Salivary excretion of rabies virus by healthy vampire bats. - Aguilar-Setien, A. (Cambridge University Press, 2005)
Salivary excretion of rabies virus was evaluated in 14 adult vampire bats (Desmodus rotundus) intramuscularly injected with a large dose (10(6) MICLD50) of vampire rabies virus variant CASS88. Saliva samples were obtained from surviving bats every other day for 30 days, then weekly for 2 months, and finally 1 and 2 years later. Rabies virus was isolated in murine neuroblastoma cells and in randomly selected cases by PCR. Rabies virus was not detected in the saliva of any of the 11 animals that succumbed (somewhat early) to rabies challenge, nor in the control bats. In contrast, virus was detected early, and only once (days 6, 6 and 21) in each of the three animals that survived rabies challenge and remained healthy for at least 2 years after challenge. At that time even vigorous dexamethasone and cyclosporine administration failed to provoke further viral excretion.